PKM: SOFTWARE MUTAKHIR (ZOTERO) UNTUK PENINGKATAN KETERAMPILAN GURU DALAM PENULISAN KARYA ILMIAH DI SMA MUHAMMADIYAH 5 MAKASSAR - Iswan Afandi; Fadly Akbar (Politeknik Negeri Sriwijaya, 2021)
This PKM activity was carried out at Muhammadiyah 5 High School in Makassar city. The problem faced is that SMA Muhammadiyah 5 teachers cannot write scientific papers using the Zotero software application. In this PKM activity, the methods of lecturing, demonstrate, question, and answer are used. PKM activities are carried out offline by implementing health protocols. The results achieved are: 1) teacher partners can download and install the Zotero software application on their laptop/PC; 2) teacher partners can make citations and bibliography using the Zotero software application; and 3) teacher partners have the skills to write scientific papers by utilizing the Zotero application.